External validation of the European Society of Thoracic Surgeons morbidity and mortality risk models. (18th March 2022) - Gómez de Antonio, David; Crowley Carrasco, Silvana; Romero Román, Alejandra; Royuela, Ana; Gil Barturen, Mariana; Obiols, Carme; Call, Sergi; Royo, Ínigo; Recuero, José Luis; Cabanero, Alberto; Moreno, Nicolás; Embún, Raúl; et al.
Abstract: OBJECTIVES: There is a wide variety of predictive models of postoperative risk, although some of them are specific to thoracic surgery, none of them is widely used. The European Society for Thoracic Surgery has recently updated its models of cardiopulmonary morbidity (Eurolung 1) and 30-day mortality (Eurolung 2) after anatomic lung resection. The aim of our work is to carry out the external validation of both models in a multicentre national database. METHODS: External validation of Eurolung 1 and Eurolung 2 was evaluated through calibration (calibration plot, Brier score and Hosmer–Lemeshow test) and discrimination [area under receiver operating characteristic curves (AUC ROC)], on a national multicentre database of 2858 patients undergoing anatomic lung resection between 2016 and 2018. RESULTS: For Eurolung 1, calibration plot showed suboptimal overlapping (slope = 0.921) and a Hosmer–Lemeshow test and Brier score of P = 0.353 and 0.104, respectively. In terms of discrimination, AUC ROC for Eurolung 1 was 0.653 (95% confidence interval, 0.623–0.684). In contrast, Eurolung 2 showed a good calibration (slope = 1.038) and a Hosmer–Lemeshow test and Brier score of P = 0.234 and 0.020, respectively. AUC ROC for Eurolung 2 was 0.760 (95% confidence interval, 0.701–0.819). CONCLUSIONS: Thirty-day mortality score (Eurolung 2) seems to be transportable to other anatomic lung-resected patients. On the other hand, postoperative cardiopulmonary morbidity score (Eurolung 1) seems not to have sufficient generalizability for new patients. Abstract : Surgical risk prediction models are an invaluable tool for assessing perioperative results, counselling patients and benchmarking [1–4].